2013
DOI: 10.1071/fp13023
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of secondary metabolites in blue lupin inoculated with Phytophthora cinnamomi following phosphite treatment

Abstract: In order to discover phytochemicals that are potentially bioactive against Phytophthora cinnamomi, (a soilborne plant pathogen) a metabolite profiling protocol for investigation of metabolic changes in Lupinus angustifolius L. plant roots in response to pathogen challenge has been established. Analysis of the metabolic profiles from healthy and P. cinnamomi-inoculated root tissue with high resolution mass spectrometry and nuclear magnetic resonance spectroscopy confirmed that although susceptible, L. angustifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…There are several up-regulated genes with GO annotations associated with flavonoid biosynthesis. Susceptible Lupinus angustifolius up-regulated the flavonoid genistein in response to P. cinnamomi (Gunning et al, 2013 ) however, certain Citrus flavonoids have an antimicrobial action against Phytophthora citrophthora (del Río et al, 2004 ). In the down-regulated dataset, GO terms associated with lignin synthesis via the phenylpropanoid pathway are over-represented.…”
Section: Discussionmentioning
confidence: 99%
“…There are several up-regulated genes with GO annotations associated with flavonoid biosynthesis. Susceptible Lupinus angustifolius up-regulated the flavonoid genistein in response to P. cinnamomi (Gunning et al, 2013 ) however, certain Citrus flavonoids have an antimicrobial action against Phytophthora citrophthora (del Río et al, 2004 ). In the down-regulated dataset, GO terms associated with lignin synthesis via the phenylpropanoid pathway are over-represented.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental plants, including Arabidopsis, Zea mays and Eucalyptus, for which comprehensive genomic information is available, are increasingly being used as host–pathogen platforms (for example, Allardyce et al ., ; Dempsey et al ., ; Rookes et al ., ). Fundamental studies on P. cinnamomi plant cell wall‐degrading enzymes and the genes that encode them are being undertaken (Hee et al ., ; Adrienne Hardham, Australian National University, Canberra, ACT, Australia, personal communication), as well as examination, at the molecular level, of defence pathways and their control (Eshraghi et al ., ; Gunning et al ., ).…”
Section: Phytophthora Cinnamomimentioning
confidence: 99%
“…), although in studies with the susceptible disease model plant Lupinus angustifolius, Gunning et al . () found that phosphite induced the production of a number of secondary metabolites that were correlated with lesion restriction and resistance to the pathogen. However, phosphite is not seen as a long‐term method to control disease as the pathogen may become resistant through the repeated use of phosphite, and toxicity has been reported in some plant species (Cahill et al .…”
Section: Introductionmentioning
confidence: 98%